Mathematical modeling of endogenous and exogenously administered T cell recirculation in mouse and its application to pharmacokinetic studies of cell therapies - Nikitich, Antonina; Helmlinger, Gabriel; Peskov, Kirill; Bocharov, Gennady (Frontiers in Immunology, 2024)
In vivo T cell migration has been of interest to scientists for the past 60 years. T cell kinetics are important in the understanding of the immune response to infectious agents. More recently, adoptive T cell therapies have proven to be a most promising approach to treating a wide range of diseases, including autoimmune and cancer diseases, whereby the characterization of cellular kinetics represents an important step towards the prediction of therapeutic efficacy. Here, we developed a physiologically-based pharmacokinetic (PBPK) model that describes endogenous T cell homeostasis and kinetics of exogenously administered T cells in mouse. We used the model to analyze the cellular kinetics for various T cell doses and frequencies of CCR7+ T cells in the population of infused lymphocytes. We predicted the effects of T cell numbers and the population composition of infused T cells on the resultant concentration of T cells in various organs. For example, a higher percentage of CCR7+ T cells among exogenously administered T lymphocytes led to an augmented accumulation of T cells in the spleen. The model predicted a linear dependence of T cell dynamics on the dose of adoptively transferred T cells. The mathematical model of T cell migration presented here can be integrated into a multi-scale model of the immune system and be used in a preclinical setting for predicting the distribution of genetically modified T lymphocytes in various organs, following adoptive T cell therapies.